Poverty targeting : money attitudes and behaviours of women in the Philippine "Gawad Kalinga" (GK - Give Care) communities : a thesis presented in partial fulfilment of the requirements for the degree of Master of Public Policy at Massey University, Auckland, New Zealand - Arawiran-Ramirez, Gilda (Massey University, 2011)
The reduction of high poverty incidence in the Philippines is a major governance objective. Poverty targeting is a strategy to identify the factors that will help the poor raise themselves from poverty. The money attitudes and behaviours of the women of the Philippine “Gawad Kalinga” showed aspects of their financial consciousness and awareness that requires, individual control and discipline, community support and policy intervention. The money attitudes and behaviours of the women in the visited communities were looked into to unveil the impact on poverty. The main research question is whether money attitudes and behaviours are poverty traps. The individual money capabilities were correlated to the workings and failures of the market and the institutions which are interconnected in the poverty problem. The research method was qualitative in nature. It was based on the interviews of 30 individuals, women residents and volunteers, of the Philippine “Gawad Kalinga” communities. The individual anecdotes disclosed opinions, attitudes, beliefs, sentiments, and emotions on their daily money struggles. The profile of the money attitudes and behaviours of the interviewees was used to determine the weaknesses that will entrap individuals in poverty. Gawad Kalinga provides a ‘protective security’ that serves as social safety net to the poor beneficiaries preventing the residents from being reduced to abject misery. The community life of the GK residents is a ‘fixed institutional arrangement’ that will serve as their support system in their daily life. Significant money attitude and behaviour issues of the residents were identified. The positive attitudes and behaviours on budgeting, savings, credit information and awareness, financial planning, community participation, and livelihood indicated high potential for poverty alleviation and achievement of well-being. The positive and constructive money attitudes and behaviours build ‘trust’ that promotes creditworthiness and provide opportunities. The negative money attitudes and behaviours such as multiple borrowings from creditors who charge high interest rates and habitual gambling will entrap individuals in poverty. The latter indicated individual development needs for community support and policy intervention.
Keywords: Gawad Kalinga communities; Poverty reduction; Women; Attitudes to money; Behaviour towards money; Philippines